Interaction of shock waves in gas dynamics: Uniform in time asymptotics - M. G. García-Alvarado; R. Flores-Espinoza; G. A. Omel'yanov (International Journal of Mathematics and Mathematical Sciences)
We construct a uniform in time asymptotics describing the interaction of two isothermal shock waves with opposite directions of motion. We show that any smooth regularization of the problem implies the realization of the stable scenario of interaction.